Spectrum of Cardiovascular Diseases in Children During High Peak Coronavirus Disease 2019 Period Infection in Northern Italy: Is There a Link?. (6th December 2020) - Fabi, Marianna; Filice, Emanuele; Andreozzi, Laura; Conti, Francesca; Gabrielli, Liliana; Balducci, Anna; Vergine, Gianluca; Cicero, Cristina; Iughetti, Lorenzo; Guerzoni, Maria Elena; Corinaldesi, Elena; Lazzarotto, Tiziana; et al.
Abstract: Background: Children with coronavirus disease-2019 (COVID-19) have a milder clinical course than adults. We describe the spectrum of cardiovascular manifestations during a COVID-19 outbreak in Emilia-Romagna, Italy. Methods: A cross-sectional multicenter study was performed, including all patients diagnosed with Kawasaki disease (KD), myocarditis, and multisystem inflammatory syndrome in children (MIS-C) from February to April 2020. KD patients were compared with those diagnosed before the epidemic. Results: KD: 8 patients (6/8 boys, all negative for severe acute respiratory syndrome coronavirus-2 [SARS-CoV-2]): complete presentation in 5/8, 7/8 immunoglobulin (IVIG) responders, and 3/8 showed transient coronary lesions (CALs). Myocarditis: one 5-year-old girl negative for SARS-CoV-2 and positive for parvovirus B19. She responded to IVIG. MIS-C: 4 SARS-CoV-2-positive boys (3 patients with positive swab and serology and 1 patient with negative swab and positive serology): 3 presented myocardial dysfunction and pericardial effusion, and 1 developed multicoronary aneurysms and hyperinflammation; all responded to treatment. The fourth boy had mitral and aortic regurgitation that rapidly regressed after steroids. Conclusions: KD, myocarditis, and MIS-C were distinguishable cardiovascular manifestations. KD did not show a more aggressive form compared with previous years: coronary involvement was frequent but always transient. MIS-C and myocarditis rapidly responded to treatment without cardiac sequelae despite high markers of myocardial injury at the onset, suggesting a myocardial depression due to systemic inflammation rather than focal necrosis. Evidence of actual or previous SARS-CoV-2 infection was documented only in patients with MIS-C. Abstract : World-wide outbreaks of Kawasaki disease and Multisystem inflammatory syndrome have been reported during the COVID-19 pandemic. We aim to provide an early characterization of the cardiovascular spectrum of manifestations, clinical course, treatment and outcomes during the COVID pandemic in Emilia-Romagna, one of the most affected by the virus.